FOOD SECURITY FIRST: THE ROLE OF WOMEN THROUGH EMPOWEREMENT FOR SUSTAINABLE FOOD, GENERAL SECURITY AND ECONOMIC DEVELOPMENT IN NIGERIA - Abdullahi, Yahya Zakari; Abdullahi, Hussainatu; Mohammed, Yelwa (European Scientific Journal, ESJ, 2012)
This paper examines the roles which women could play if they are effectively empowered towards resolving the problem of food security that will guarantee an enduring and sustainable general security and economic development in Nigeria. The paper examines the issues such as; the issue of food security situation in Nigeria, general security challenges in recent times in Nigeria, as well as the economic implication of general security challenges on food security in Nigeria. The methodological approach adopted in writing this paper is content analysis. The paper found that livelihood initiatives aimed at protecting and promoting food security could be achieved through women’s empowerment in agricultural production, small scale businesses and any other forms of employment. This will consequently lead to food security, prevent dependency, reduce vulnerability to social vices, enhance self reliance and development of specific skills leading to improvement of the general well being of the people, culminating in sustainable economic development. The paper therefore recommends among other things, that there is need for proper understanding of the inter-connectedness of women and household food security in targeting and designing intervention mechanisms that would lead to improvement in a variety of well being and outcomes for the entire family, community and society at large.